Analyzing the Rights of Fostered Children at LPKA Class II Yogyakarta - Widya Islami, Desita Nanda; Isnawan, Fuadi (JUSTITIA JURNAL HUKUM, 2024)
This research delves into the exploration of fostered children's rights discovery at LPKA Class II Yogyakarta, recognizing that children under guardianship are entitled to various rights as stipulated by law. Despite legal provisions, there remains a gap between theoretical entitlements and practical implementation within LPKA Class II Yogyakarta, necessitating an in-depth investigation. The study aims to scrutinize the extent to which fostered children's rights fulfilled. It also seeks to analyze the obstacles faced by LPKA Class II Yogyakarta officers in fulfilling these rights. The research will empirically examine the fulfillment of children's rights and the challenges encountered within LPKA Class II Yogyakarta through interviews with LPKA Class II Yogyakarta officers provide firsthand insights into policy implementation and challenges encountered in upholding fostered children's rights. The research findings highlight significant gaps in the fulfillment of subsidiary rights for detainees, particularly in education, healthcare, and access to reading materials. While efforts have been made to address some aspects of detainee rights, such as nutrition and religious practices, deficiencies persist in critical areas. Limited educational resources, inadequate healthcare services, and a dearth of reading materials pose significant challenges to fostered children's well-being and rehabilitation. Additionally, obstacles such as the absence of in-house schooling, insufficient medical personnel, and limited library resources further impede the realization of children's rights within LPKA Class II Yogyakarta.